The Probabilistic Method for Determination the Inertia Characteristics of 3D Bodies with Monte Carlo Algorithms - BOTIȘ, Marius; PLEȘCAN, Costel (Universitatea Dunarea de Jos din Galati, 2022)
This study determines the inertial characteristics of bodies with probabilistic algorithms of the Monte Carlo type. To determine the mechanical moments of inertia in the case of three-dimensional bodies, the bodies are decomposed into simple bodiesfor which the moments of inertia are calculated, which are added to Steiner's relations. If the bodies have complex shapes to determine the moments of mechanical inertia, numerical or probabilistic algorithms can be used. This paper presents the main stagesin the use of probabilistic algorithms for calculating moments of inertia and finally a program in MATLAB that allows determining the moments of inertia for bodies.